Exploring the Outcomes of Divergent Approaches to the Policy Making Process: Domestic Violence Disclosure Schemes and Perpetrator Registers in Australia - Fitz-Gibbon, Kate; Walklate, Sandra; Reeves, Ellen (feminists@law, 2024)
In April 2021 an Australian Government Inquiry recommended the Australian government commission research to explore the benefits and risks of the introduction of a publicly accessible register of convicted domestic, family and sexual violence perpetrators. At the time of the Inquiry’s recommendation, only one Australian jurisdiction had a domestic violence disclosure scheme (DVDS) in operation and no state had a publicly accessible sex offender register. A public register, if implemented, would represent a significant shift in the approach taken to achieving perpetrator accountability and better ensuring women’s safety. This article traces the decade leading up to this recommendation and the significant variance in policy and practice across Australian state and territory jurisdictions. To do so, it critically analyses the outcomes of two major state-level inquiries, which did not recommend the introduction of a DVDS or a public offender register. These case studies are presented alongside a contrasting case study of two other Australian states which, following the introduction of a DVDS in England and Wales, have adopted a DVDS with the stated objective of improving women’s safety through the provision of greater information about perpetrator histories and risk. The analysis draws together these case studies to question how the national-level inquiry arrived at its recommendation in the absence of either the effectiveness of DVDSs being established or clear advocacy in support of a public registry model in Australia. This Australian experience presents valuable learning on the policy-making process and the shifting reliance on evidence-based reform in lieu of publicly favoured punitive responses to domestic, family and sexual violence. The article calls for a return to principled policy making processes, underpinned by a commitment to delivering policy and practice that is seamless, accessible, fair and effective.